2018
DOI: 10.1002/chem.201804155
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Core–Shell Nanoparticles by “Plug and Play” Self‐Assembly

Abstract: Supramolecular hybrid functional nanoparticles (NPs) can be obtained via the colloidal tectonics approach provided that multiple interactive molecular tectons are used. Herein, the programmable synthesis of novel hybrid core–shell nanoparticles via the following sequential steps is reported: (i) complexation of 1‐decanol by the β‐cyclodextrin (β‐CD), (ii) spontaneous self‐assembly into CD NPs, (iii) adsorption of polyoxometalate anions, PW12O403−, on the polar neutral interface of the CD NPs. Such an approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…The titration of 4 mM β-CD solution by {PMo12} is shown in Figure 3, and compares well with that obtained with {PW12}, shown in Figure S2, in SI. 26 The six types of protons Monitoring hydrolytic stability by 31 P NMR. The stability of PW12O40 3in pure water and in presence of two eq.…”
Section: Titration Of Cds With Pomsmentioning
confidence: 99%
See 2 more Smart Citations
“…The titration of 4 mM β-CD solution by {PMo12} is shown in Figure 3, and compares well with that obtained with {PW12}, shown in Figure S2, in SI. 26 The six types of protons Monitoring hydrolytic stability by 31 P NMR. The stability of PW12O40 3in pure water and in presence of two eq.…”
Section: Titration Of Cds With Pomsmentioning
confidence: 99%
“…The supramolecular interactions between Keggin POMs and CDs in solution can be studied and followed, primarily by nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry. 16,22,25,26 However, these studies have rarely been conducted in POM stabilization context and no systematic pH study has been reported so far. The scope of this report will then focus on the impact of this crucial parameter, namely pH, for the POMs chemistry, hitherto ignored in previous studies about POM-CD systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the development of smart nanoparticles has made it possible to efficiently recover catalysts in the Pickering interfacial catalytic system with less work time of external field and no reagent introduction. This concept provides a green and an efficient way for combination of enhancement of oxidation reaction and the rapid recovery of nanocatalysts in the biphasic reaction, avoiding the generation of toxic byproducts and the complex and energy-consuming recycling operation. …”
Section: Resultsmentioning
confidence: 99%
“…Our first proposal is that the anionic catalyst lies in the aqueous phase, contrary to the Pickering catalytic systems based on amphiphilic dodecyltrimethylammonium/PW 12 O 40 NPs (see above). However, our recent investigations prove that the PW 12 O 40 3− anions have a propensity to adsorb on electrically neutral surfaces of CD/oil NPs due to their large, sticky, polarizable, and salting-in nature, leading to supramolecular hybrid core-shell CD/oil@PW 12 O 40 NPs via the "colloidal tectonics" approach [233]. These Pickering emulsions, based on hybrid NPs, behave as a highly efficient reaction medium.…”
Section: Pickering Emulsionsmentioning
confidence: 98%